Standard sample for carbon, oxygen and nitrogen in zirconium and preparation method thereof

By mixing sponge zirconium, zirconia and chromium carbide in proportion, and using vacuum consumable arc furnace smelting and multiple forging treatments, a stable and accurate fixed value standard sample was prepared, and the existing zirconium was solved. The problem of insufficient uniformity and stability of standard samples of C, O and N elements in the C, O and N elements meets the detection needs of nuclear power projects.

CN119144874APending Publication Date: 2024-12-17STATE NUCLEAR ZIRCONIUM & HAFNIUM PHYSICAL & CHEMICAL TESTING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423024.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the development of nuclear power projects, the lack of stable and accurate standard samples of C, O and N elements in zirconium, which affects the quality control and composition analysis of zirconium materials. The existing samples lack uniformity and stability, which is difficult to meet. Test requirements.

Method used

Using sponge zirconium, zirconia and chromium carbide in proportion, and after vacuum consumable electric arc furnace melting, forging, hot rolling, cold drawing and pickling treatment, the C, O and N element contents are prepared from 0.0030 to 0.0070% and 0.05 ~0.10%, 0.0020-0.0040% of zirconium medium carbon-oxynitrogen standard samples were ensured through multiple peeling treatments and initial uniformity inspection.

Benefits of technology

The prepared zirconium standard samples have good uniformity, high stability, and accurate setting values. They are suitable for the analysis and detection of C, O and N elements in zirconium. They solve the problem of lack of existing samples and are used for instruments and Calibration provides a basis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081382780000051
    Figure BDA0005081382780000051
  • Figure BDA0005081382780000052
    Figure BDA0005081382780000052
  • Figure BDA0005081382780000061
    Figure BDA0005081382780000061
Patent Text Reader

Abstract

The invention belongs to the technical field of zirconium alloy, and particularly relates to a standard sample for carbon, oxygen and nitrogen in zirconium and a preparation method thereof. The standard sample of carbon, oxygen and nitrogen in zirconium provided by the invention comprises the following elements in percentage by weight: 0.0030 to 0.0070 percent of C, 0.05 to 0.10 percent of O and 0.0020 to 0.0040 percent of N. The standard sample provided by the invention has the advantages of uniform components, good stability and accurate fixed value, and can be used for correcting the determination results of C, O and N elements in zirconium and monitoring the state of instruments and equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zirconium alloys, and in particular relates to a carbon, oxygen and nitrogen standard sample in zirconium and a preparation method thereof. Background Art

[0002] Zirconium metal has the advantages of high melting point, small thermal neutron absorption cross-section, ultra-high strength and hardness, strong corrosion resistance and excellent nuclear properties. It is widely used in nuclear reactor core structural materials and nuclear fuel assembly cladding materials, aerospace, military atomic energy fields.

[0003] With the increase and construction of nuclear power projects, the demand for zirconium research and production has increased, and the corresponding demand for standard samples of C, O, and N elements in zirconium in the testing industry has also gradually increased. This standard sample is a necessary support for zirconium product quality control and component analysis. It is an effective means to standardize the component detection methods and value unification in the process of zirconium research, production, and application. Therefore, it is increasingly important to prepare standard samples of C, O, and N elements in zirconium that meet the use requirements. Summary of the invention

[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0005] In view of the massive increase and construction of nuclear power projects, it is urgently necessary to develop standard samples of nuclear-grade zirconium C, O, and N components. This will also help to further promote the research and development and application of zirconium materials, effectively improve the detection and analysis efficiency of products, unify industry measurement standards, better serve the zirconium metal industry, and solve the demand for standard samples in the development of the zirconium industry.

[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiment of the present invention provides a standard sample of carbon, oxygen and nitrogen in zirconium, which has good stability and accurate fixed value, and can be used for the correction of the determination results of C, O and N elements in zirconium and the monitoring of the status of instruments and equipment.

[0007] The carbon, oxygen and nitrogen standard sample in zirconium according to the embodiment of the present invention comprises C, O and N elements, wherein C: 0.0030-0.0070%, O: 0.05-0.10%, N: 0.0020-0.0040%, calculated in weight percentage.

[0008] The advantages and technical effects brought by the standard samples of carbon, oxygen and nitrogen in zirconium in the embodiments of the present invention are as follows: 1. The standard samples in the embodiments of the present invention have good uniformity of composition, good stability and high accuracy, and can meet the relevant requirements for standard samples; 2. The standard samples in the embodiments of the present invention are suitable for the analysis and detection of C, O and N elements in zirconium, which solves the problem of the current lack of standard samples of C, O and N elements in zirconium, and provides a basis for the use and calibration of instruments.

[0009] In some embodiments, the standard sample further includes: iron: 0.0530-0.0555%, chromium: 0.0090-0.0110%, calculated in weight percentage.

[0010] The embodiment of the present invention also provides a method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium, comprising the following steps:

[0011] (1) Sponge zirconium, zirconium oxide and chromium carbide are mixed in proportion and pressed into an electrode block, and then welded into an electrode, wherein the mass ratio of the sponge zirconium, zirconium oxide and chromium carbide is 5640-5660:1.8-2.2:1;

[0012] (2) melting the electrode obtained in step (1) into an ingot in a vacuum consumable arc furnace and performing a peeling process, wherein the melting current in the vacuum consumable arc furnace is 6 to 12 KA and the vacuum degree is ≤ 3 Pa;

[0013] (3) subjecting the ingot subjected to the peeling treatment in step (2) to forging treatment, peeling treatment again, and taking samples for preliminary uniformity inspection;

[0014] (4) The forged bars that have passed the initial uniformity inspection in step (3) are subjected to forging, hot rolling, cold drawing and pickling.

[0015] The advantages and technical effects brought by the preparation method of the standard sample of carbon, oxygen and nitrogen in zirconium of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention selects suitable raw materials and adopts vacuum melting and multiple peeling treatments to make the prepared standard samples of C, O and N in zirconium have uniform composition, good stability and accurate fixed value; 2. The method of the embodiment of the present invention limits the current and vacuum degree of vacuum consumable melting, so that the prepared standard samples meet the design target value and have good uniformity; 3. The standard samples of C, O and N elements in zirconium prepared by the method of the embodiment of the present invention are suitable for the analysis and detection of C, O and N elements in zirconium, which solves the problem of the current lack of standard samples of C, O and N elements in zirconium and provides a basis for the use and calibration of instruments.

[0016] In some embodiments, in step (1), the mass ratio of the zirconium sponge, zirconium oxide and chromium carbide is 5650-5655:1.9-2.0:1.

[0017] In some embodiments, in step (1), the welding is performed by plasma welding box, the welding current is 2-3KA, the vacuum degree of the plasma welding box is ≤3Pa, the welding voltage is 26-31V, and the cooling time is ≥30min.

[0018] In some embodiments, in the step (2), at least three smeltings are performed in the vacuum consumable arc furnace, and the head and tail are swapped after each smelting.

[0019] In some embodiments, in step (2) and / or step (3), the depth of the peeling process is 5 to 10 mm.

[0020] In some embodiments, in step (3), the temperature of the forging process is (850-1050)°C.

[0021] In some embodiments, in the step (3), the C content in the initial uniformity inspection is detected and analyzed using a LECO carbon-sulfur analyzer, and the O and N contents are detected and analyzed using a LECO nitrogen-oxygen analyzer.

[0022] In some embodiments, in step (4), the temperature of the forging process is (850-1050)°C;

[0023] And / or, the temperature of the hot rolling treatment is (610-630)°C;

[0024] And / or, the cold drawing treatment includes drawing the hot-rolled zirconium wire again at room temperature to a diameter of (2-4) mm;

[0025] And / or, the acid solution used in the pickling treatment is a mixed solution of nitric acid, hydrofluoric acid and deionized water. DETAILED DESCRIPTION

[0026] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0027] The carbon, oxygen and nitrogen standard sample in zirconium according to the embodiment of the present invention comprises C, O and N elements, wherein C: 0.0030-0.0070%, O: 0.05-0.10%, N: 0.0020-0.0040%, calculated in weight percentage.

[0028] The carbon, oxygen and nitrogen standard samples in zirconium in the embodiments of the present invention have good uniformity of composition, good stability and high accuracy, and can meet the relevant requirements for standard samples; the standard samples in the embodiments of the present invention are suitable for the analysis and detection of C, O and N elements in zirconium, which solves the problem of the current lack of standard samples for C, O and N elements in zirconium, and provides a basis for the use and calibration of instruments.

[0029] In some embodiments, preferably, the standard sample also includes: iron: 0.0530-0.0555%, chromium: 0.0090-0.0110%, calculated in weight percentage.

[0030] The embodiment of the present invention also provides a method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium, comprising the following steps:

[0031] (1) Sponge zirconium, zirconium oxide and chromium carbide are mixed in proportion and pressed into an electrode block, and then welded into an electrode, wherein the mass ratio of the sponge zirconium, zirconium oxide and chromium carbide is 5640-5660:1.8-2.2:1;

[0032] (2) melting the electrode obtained in step (1) into an ingot in a vacuum consumable arc furnace and performing a peeling process, wherein the melting current in the vacuum consumable arc furnace is 6 to 12 KA and the vacuum degree is ≤ 3 Pa;

[0033] (3) subjecting the ingot subjected to the peeling treatment in step (2) to forging treatment, peeling treatment again, and taking samples for preliminary uniformity inspection;

[0034] (4) The forged bars that have passed the initial uniformity inspection in step (3) are subjected to forging, hot rolling, cold drawing and pickling.

[0035] The method for preparing the standard sample of carbon, oxygen and nitrogen in zirconium of the embodiment of the present invention selects suitable raw materials and adopts vacuum melting and multiple peeling treatments, so that the prepared standard sample of C, O and N in zirconium has uniform composition, good stability and accurate fixed value; the method of the embodiment of the present invention limits the current and vacuum degree of vacuum consumable melting, so that the prepared standard sample meets the design target value and has good uniformity; the standard sample of C, O and N elements in zirconium prepared by the method of the embodiment of the present invention is suitable for the analysis and detection of C, O and N elements in zirconium, solves the problem of the current lack of standard samples of C, O and N elements in zirconium, and provides a basis for the use and calibration of instruments.

[0036] If the current of vacuum consumable melting is too small or too large, the melting cannot be completely stable; if the vacuum degree of vacuum consumable melting is too low or too high, the uniformity of the prepared standard sample is poor, and the oxygen and nitrogen contents cannot reach the designed target values.

[0037] In some embodiments, preferably, in step (1), the mass ratio of the zirconium sponge, zirconium oxide and chromium carbide is 5650-5655: 1.9-2.0: 1. Further preferably, the mass ratio of the zirconium sponge, zirconium oxide and chromium carbide is 5652.2: 1.96: 1.

[0038] In some embodiments, preferably, in the step (1), the welding is performed by plasma welding box, the welding current is 2-3KA, the vacuum degree of the plasma welding box is ≤3Pa, the welding voltage is 26-31V, and the cooling time is ≥30min.

[0039] In some embodiments, preferably, in step (2), at least three smeltings are performed in the vacuum consumable arc furnace, and the head and tail are swapped after each smelting. The head and tail swapping means that the head of the ingot is loaded into the bottom position when charging before the second smelting, and the cycle is repeated in sequence.

[0040] In the embodiment of the present invention, multiple vacuum melting processes are adopted, and the head and tail are interchanged during the melting process, which can further ensure that the prepared standard sample has good uniformity of composition, good stability and high accuracy.

[0041] In some embodiments, preferably, in step (2) and / or step (3), the depth of the peeling process is 5 to 10 mm.

[0042] In some embodiments, preferably, in the step (3), the temperature of the forging treatment is (850-1050)°C.

[0043] In some embodiments, preferably, in the step (3), the C content in the initial uniformity inspection is detected and analyzed using a LECO carbon-sulfur analyzer, and the O and N contents are detected and analyzed using a LECO nitrogen-oxygen analyzer.

[0044] In some embodiments, preferably, in the step (4), the temperature of the forging process is (850-1050)°C;

[0045] And / or, the temperature of the hot rolling treatment is (610-630)°C;

[0046] And / or, the cold drawing treatment includes drawing the hot-rolled zirconium wire again at room temperature to a diameter of (2-4) mm;

[0047] And / or, the acid solution used in the pickling treatment is a mixed solution of nitric acid, hydrofluoric acid and deionized water. Further preferably, the cold drawing treatment is performed at least twice; the concentration of nitric acid used in the acid solution is 40-50%, the concentration of hydrofluoric acid is 40-50%, and the volume ratio of nitric acid, hydrofluoric acid and deionized water is (10-1): (0.9-1.1): (7-9);

[0048] And / or, the cold drawing and washing treatment includes washing the hot-rolled zirconium wire in an acid solution, then washing it with deionized water for at least three times, and drying it with cold air.

[0049] In some embodiments, preferably, the step (4) further comprises cutting the pickled sample into a block standard sample of Φ2mm×4mm, and performing a uniformity test and a stability test, and determining the value of the standard sample that passes the uniformity test. Further preferably, the uniformity test is performed in accordance with YS / T 409-2012 "Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products", the stability test is performed in accordance with YS / T 409-2012 "Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products", and the determination comprises determining the value of the standard sample that passes the composition uniformity test, and the result is processed in accordance with the requirements of YS / T409-2012 "Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products", and rounded in accordance with GB / T 8170-2008 "Numerical Rounding Rules and Representation and Determination of Limit Values", and the obtained data is the standard value of the standard sample of C, O, and N elements in zirconium.

[0050] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0051] Example 1

[0052] (1) 130 kg of zirconium sponge, 0.045 kg of zirconium oxide and 0.023 kg of chromium carbide (the mass ratio of zirconium sponge, zirconium oxide and chromium carbide is 5652.2:1.96:1) are mixed evenly and pressed into an electrode block, and then welded into an electrode using a vacuum plasma welding box, wherein the welding current is 3 KA, the vacuum degree of the plasma welding box is 1.7 Pa, the welding voltage is 26-31 V, and the welding is performed, and the cooling is performed for 41 minutes after the welding is completed;

[0053] (2) The electrode obtained in step (1) is melted three times in a vacuum consumable arc furnace to form an ingot, and the head and tail are swapped after each melting. The melting current is 9KA and the vacuum degree is 2Pa. Then, the skin is peeled off by 10mm.

[0054] (3) After forging the ingot subjected to the peeling treatment in step (2) at 900° C., the ingot is peeled again by 10 mm;

[0055] (4) Initial inspection of uniformity: Take samples at 3 points (9 points in total) along the radius of the upper end face, the radius of the lower end face and the side wall of the forged rod obtained after peeling. The C content is measured by LECO's carbon-sulfur tester, and the O and N contents are measured by LECO's nitrogen-oxygen tester. The uniformity initial inspection samples are tested and analyzed. The inter-laboratory allowable difference (Δ) of each element content is compared with the standard deviation (s) of a limited number of measurements. When 1.5s≤1 / 2Δ, it is considered to be qualified in the initial inspection. When 1.5s>1 / 2Δ, it is considered to be unqualified in the initial inspection. The results are shown in Table 1.

[0056] Table 1 Statistics of the initial inspection results of standard sample uniformity (%)

[0057]

[0058] (5) The forged rod that has passed the initial uniformity inspection in step (4) is subjected to forging treatment, hot rolling treatment, cold drawing treatment, and pickling treatment, wherein the temperature of the forging treatment is 950° C., the temperature of the hot rolling treatment is 620° C., the cold drawing treatment includes drawing the hot-rolled zirconium wire again at room temperature to a diameter of 3 mm, and the pickling treatment includes washing the cold-drawn zirconium wire in a pickling solution, then washing it three times with deionized water, and drying it with cold air, wherein the acid solution is prepared by using 40% nitric acid, 50% hydrofluoric acid and deionized water in a volume ratio of 11:1:8.

[0059] (6) The acid-washed filamentary samples were cut into block-shaped standard samples with a diameter of 2 mm × 4 mm, screened, washed three times with anhydrous ethanol, naturally air-dried, mixed, weighed and packaged. The packaging unit was 200 tablets / bottle, each tablet was 0.1 g, and a total of 300 bottles were prepared.

[0060] The standard sample prepared in Example 1 was subjected to uniformity test, stability test and value determination.

[0061] (1) Homogeneity test: According to YS / T 409-2012 Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products, the element content of the sample was determined and the uniformity of the standard sample composition was checked. Fifteen samples were randomly selected as homogeneity test samples, numbered in sequence, and the data were analyzed and counted using the one-way analysis of variance. Each sample was measured three times in accordance with the following scheme:

[0062] First time: 1-3-5-7-9-11-13-15-2-4-6-8-10-12-14

[0063] Second time: 15-14-13-12-11-10-9-8-7-6-5-4-3-2-1

[0064] Third time: 2-4-6-8-10-12-14-1-3-5-7-9-11-13-15

[0065] The one-way analysis of variance (F test) was used to perform statistical analysis on the uniformity test results. The statistics of the uniformity test results are shown in Table 2. From the statistical results, it can be seen that the F values ​​of the three elements are less than the critical value of 2.04, and the uniformity test is qualified.

[0066] Table 2 Statistics of uniformity test results of standard samples

[0067]

[0068] (2) Stability test: Standard samples that passed the uniformity test were subjected to stability test in accordance with the requirements of YS / T 409-2012 Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products. Two samples were randomly selected and tested using the fixed value method. Stability monitoring was performed six times within four months. The t-test method was used as the statistical method for stability analysis. The statistical results of the stability test are shown in Table 3.

[0069] Table 3 Statistics of stability test results

[0070]

[0071] The stability of this standard sample was monitored 6 times within 4 months, and the t value test results were all less than the critical value t (0.05,5) =2.57, the sample is stable.

[0072] (3) Value determination: The standard samples that passed the composition uniformity test were sent to eight units with the qualification of standard sample value determination for value determination. The results were processed in accordance with the requirements of YS / T 409-2012 "Technical Specifications for Standard Samples for Analysis of Nonferrous Metal Products" and rounded according to GB / T 8170-2008 "Rules for Rounding off of Numerical Values ​​and Expression and Determination of Limit Values". The obtained data are the standard values ​​of the standard samples of C, O and N elements in zirconium.

[0073] The standard value, standard deviation and expanded uncertainty of this standard sample are shown in Table 4.

[0074] Table 4 The results of the standard sample determination

[0075]

[0076] Comparative Example 1

[0077] The preparation method of this comparative example is the same as that of Example 1, except that in step (1), the amounts of zirconium sponge, zirconium oxide and chromium carbide are 124.5 kg, 0.1 kg and 0.025 kg respectively, that is, the mass ratio of zirconium sponge, zirconium oxide and chromium carbide is 4980:4:1.

[0078] In the standard sample prepared in this comparative example, the mass percentage contents are: C = 0.008%, O = 0.12%, N = 0.0020%, Fe = 0.0528%, Cr = 0.0091%, which obviously cannot meet the requirements of the standard sample.

[0079] Comparative Example 2

[0080] The preparation method of this comparative example is the same as that of Example 1, except that in step (2), when the current of the smelting in the vacuum consumable arc furnace is 5KA and the vacuum degree is 5Pa, the initial uniformity inspection of the obtained standard sample does not meet the standard requirements (i.e., 1.5*SD is greater than 1 / / 2Δ), and the data are shown in Table 5.

[0081] Table 5 Preliminary inspection results of standard sample uniformity (%)

[0082]

[0083] The present invention adopts scientific and reasonable component design, accurate batching calculation, strict process quality control, uses sponge zirconium, zirconium oxide, chromium carbide, electrode welding, three vacuum arc furnace melting, forging, hot rolling, cold drawing, pickling, shearing, screening, cleaning, packaging finished products, uniformity inspection, stability inspection, and uses multiple units to cooperate and accurately determine the value and scientific and reasonable mathematical statistics methods to calculate the standard value and expanded uncertainty of the standard sample. Experiments show that the standard sample of C, O, and N elements in zirconium prepared by the method provided by the present invention has uniform composition, good stability, and accurate determination, and can be used for the correction of the determination results of C, O, and N elements in zirconium and the monitoring of the status of instruments and equipment.

[0084] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0085] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A standard sample of carbon, oxygen and nitrogen in zirconium, characterized in that: It includes C, O, and N elements, wherein C: 0.0030-0.0070%, O: 0.05-0.10%, and N: 0.0020-0.0040%, calculated in weight percentage.

2. The standard sample of carbon, oxygen and nitrogen in zirconium according to claim 1, characterized in that: The standard sample also Comprising: Iron: 0.0530-0.0555%, chromium: 0.0090-0.0110%, calculated in weight percentage.

3. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 1 or 2, characterized in that: The following steps are involved: (1) Sponge zirconium, zirconium oxide and chromium carbide are mixed in proportion and pressed into an electrode block, and then welded into an electrode, wherein the mass ratio of the sponge zirconium, zirconium oxide and chromium carbide is 5640-5660:1.8-2.2:1; (2) melting the electrode obtained in step (1) into an ingot in a vacuum consumable arc furnace and performing a peeling process, wherein the melting current in the vacuum consumable arc furnace is 6 to 12 KA and the vacuum degree is ≤ 3 Pa; (3) subjecting the ingot subjected to the peeling treatment in step (2) to forging treatment, peeling treatment again, and taking samples for preliminary uniformity inspection; (4) The forged bars that have passed the initial uniformity inspection in step (3) are subjected to forging, hot rolling, cold drawing and pickling.

4. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In the step (1), the mass ratio of the zirconium sponge, zirconium oxide and chromium carbide is 5650-5655:1.9-2.0:

1.

5. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In the step (1), the welding is performed by plasma welding box, the welding current is 2-3KA, the vacuum degree of the plasma welding box is ≤3Pa, the welding voltage is 26-31V, and the cooling time is ≥30min.

6. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In the step (2), at least three smeltings are performed in the vacuum consumable arc furnace, and the head and tail are swapped after each smelting.

7. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In step (2) and / or step (3), the depth of the peeling process is (5 to 10) mm.

8. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In the step (3), the temperature of the forging process is (850-1050)°C.

9. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3 or 8, characterized in that: In the step (3), the C content in the initial uniformity inspection is detected and analyzed using a LECO carbon-sulfur analyzer, and the O and N contents are detected and analyzed using a LECO nitrogen-oxygen analyzer.

10. The method for preparing a standard sample of carbon, oxygen and nitrogen in zirconium according to claim 3, characterized in that: In the step (4), the temperature of the forging process is (850-1050)°C; And / or, the temperature of the hot rolling treatment is (610-630)°C; And / or, the cold drawing treatment includes drawing the hot-rolled zirconium wire again at room temperature to a diameter of (2-4) mm; And / or, the acid solution used in the pickling treatment is a mixed solution of nitric acid, hydrofluoric acid and deionized water.